Security system using controller area network (CAN) bus - Esro, Mazran; Abdul Manap, Redzuan; Ahmad, Badrul Hisham; Mohd Khafe, Adie; Basari, Amat Amir (Penerbit Universiti, UTeM, 2009)
Controller Area Network (CAN) has long been used for automotive applications as a method to enable robust serial communication. The goal was to make the system more reliable, safe and efficient while decreasing wiring harness weight and complexity. Based on these factors, a CAN bus project was carried out to fully utilize the application of CAN bus system in building automation, security system and data acquisition system. This report shall focus on application of CAN bus in security system.